(untitled) (The Research of Medical Science Review, 2025)
This study investigates the relationship between depression and migraine headaches. A total of 151 participants showed that major depressive disorder patients experienced more frequent and intense migraine attacks lasting more extended periods than those with low or no depression symptoms. The studied data shows significant relationships exist between depression intensities and migraine features and reveals that depression coexistence occurs often in patients of migraine. The study shows that outcome of the headache and treatment response depends on depression intensity and patient age together with their gender and family health history along with migraine duration. Patients performance in migraine management reduced when they suffered from severe grades of depression. An assessment of a patient's mental health should become part of migraine treatment care but requires complete treatment solutions to be most effective. Improved health outcomes are achievable when healthcare professionals understand the link between depression and migraine, which results in better patient care and superior health outcomes.